State Registration of Securities: An Anachronism No Longer Viable - Charles H. B. Braisted (Washington University Law Quarterly, 2000)
A number of articles and treatises give a detailed recitation of the history of blue sky laws, the reasoning behind the different approaches taken by federal and state legislators, and the arguments for and against each. There is no need to rehash the arguments here, pro or con. A cursory review of certain developments of the last fifteen years might be in order, however.
Keywords: Blue sky laws; Exclusive & concurrent legislative powers; Securities law; Securities Litigation Uniform Standards Act of 1998